Zwitterionic microporous polymer with selective ion transport for durable lithium-sulfur batteries. (17th January 2022) - Sun, Shuzheng; Li, Congcong; Li, Mingkai; Gu, Guoxian; Yang, Yanqin; Li, jingde; Zhang, Zisheng
Abstract: Functional separator which facilitates the fast transport of Li + but obstructs the permeation of polysulfides is highly required for durable lithium-sulfur (Li-S) batteries. Here, we report a facile approach to developing such functional separator by coating the commercial polypropylene separator with a unique solution-processable polymer featuring both intrinsic microporosity and ion-selective functionality. The polymer is designed with contorted and rigid backbones, which incorporates zwitterionic side chains with both sulfophilic and lithiophilic groups, to produce confined ionic channels for selective ion transport via the chemical interactions with lithium polysulfides. Therefore, when used in the cell configuration, the as-developed functional separator can not only allow the fast Li + conduction but also obstruct the penetration of bulky polysulfides, thus resulting in obvious shuttle suppression as well as the resultant credible and stable sulfur electrochemistry. Thanks to these advantages, the Li-S batteries implementing the as-developed functional separator possess high cycling ability and decent rate performance. Graphical abstract: Image 1 Highlights: A novel zwitterionic microporous polymer QTB-SA is successfully prepared. QTB-SA/PP separator is fabricated by coating QTB-SA on polypropylene membrane. This separator can allow fast Li +  transfer but obstruct polysulfide permeation. The resultant Li-S battery shows excellent cyclability and decent rate performance.